The effect of meteorological conditions on aerosol size distribution in Istanbul - Kuzu, S. Levent; Saral, Arslan (SPRINGER, 2017)
Ambient aerosols were sampled by a high-volume cascade impactor in Istanbul, through May 2012 and November 2014. Seventy-eight size-segregated samples were gathered within the period at six different stages. The particles exhibited tri-modal distribution. The peak at 7.2 and 7.2-3 mu m had a strong relation, indicating same sources. Increased relative humidity enriched 0.95-1.5-mu m particle fraction in winter. Particles between 0.49 and 3 mu m were inversely related to ambient temperature. Dilution effect of the wind was significant for PM1.5. Wind acted as a source for larger particles by carrying them from other source regions. Multiple linear regression was applied to particulate matter fractions in order to model the concentrations of each fraction related to meteorological data. In the model, the particle fractions of 1.5-0.95 and 0.95-0.49 mu m exhibited the highest prediction performance.
Keywords: Particle size distribution; Respirable fraction; Thoracic fraction; Pearson's correlation coefficient; MLR; PSCF; POLYCYCLIC AROMATIC-HYDROCARBONS; AIRBORNE PARTICULATE MATTER; AIR-POLLUTION; CHEMICAL-COMPOSITION; SEASONAL-VARIATION; HEALTH IMPACT; MASS CLOSURE; URBAN; PM2.5; MORTALITY; Environmental Sciences & Ecology